Overweight and Obesity are Risk Factors of Severe Illness in Patients with COVID‐19. Issue 11 (23rd September 2020) - Wang, Jian; Zhu, Li; Liu, Longgen; Zhao, Xiang‐an; Zhang, Zhaoping; Xue, Leyang; Yan, Xuebing; Huang, Songping; Li, Yang; Cheng, Juan; Zhang, Biao; Xu, Tianmin; et al.
Abstract : Objective: This study aimed to observe the clinical characteristics of patients with coronavirus disease 2019 (COVID‐19) with overweight and obesity. Methods: Consecutive patients with COVID‐19 from 10 hospitals of Jiangsu province, China, were enrolled. Results: A total of 297 patients with COVID‐19 were included, and 39.39% and 13.47% of patients had overweight and obesity, respectively. The proportions of bilateral pneumonia (92.50% vs. 73.57%, P = 0.033) and type 2 diabetes (17.50% vs. 3.57%, P = 0.006) were higher in patients with obesity than lean patients. The proportions of severe illness in patients with overweight (12.82% vs. 2.86%, P = 0.006) and obesity (25.00% vs. 2.86%, P < 0.001) were significantly higher than lean patients. More patients with obesity developed respiratory failure (20.00% vs. 2.86%, P < 0.001) and acute respiratory distress syndrome (5.00% vs. 0%, P = 0.024) than lean patients. The median days of hospitalization were longer in patients with obesity than lean patients (17.00 days vs. 14.00 days, P = 0.029). Overweight (OR, 4.222; 95% CI: 1.322‐13.476; P = 0.015) and obesity (OR, 9.216; 95% CI: 2.581‐32.903; P = 0.001) were independent risk factors of severe illness. Obesity (HR, 6.607; 95% CI: 1.955‐22.329; P = 0.002) was an independent risk factor of respiratory failure. Conclusions: Overweight and obesity were independent risk factors of severe illness in COVID‐19 patients. More attention should be paid to these patients.